2007
DOI: 10.1007/s11142-007-9043-2
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of SFAS No. 130 comprehensive income disclosures

Abstract: In this study, we provide evidence on the pricing of other comprehensive income (OCI) that differs from most evidence in prior research. Prior archival research has largely concluded that OCI is not priced by investors. In contrast, we provide evidence in the post-SFAS 130 period that OCI is priced on a dollar-fordollar basis as is predicted by economic theory for transitory income items. We attribute this finding to our use of post-SFAS 130 as-reported measures of OCI rather than pre-SFAS 130 as-if estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
225
2
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(269 citation statements)
references
References 29 publications
22
225
2
17
Order By: Relevance
“…All other firm-specific data are obtained from COMPUSTAT. Our data collection for independent variables also conform to the observations of Chambers et al (2007) that investors pay greater attention to OCI items that are reported in the statement of changes in stockholders' equity rather than in a statement of financial performance. Considering the data availability from the above sources, our final sample includes 697 firms comprising 283 S&P large, 212 S&P mid-cap and 202 S&P small cap firms.…”
Section: Sample Descriptive Data and Correlationsmentioning
confidence: 55%
See 4 more Smart Citations
“…All other firm-specific data are obtained from COMPUSTAT. Our data collection for independent variables also conform to the observations of Chambers et al (2007) that investors pay greater attention to OCI items that are reported in the statement of changes in stockholders' equity rather than in a statement of financial performance. Considering the data availability from the above sources, our final sample includes 697 firms comprising 283 S&P large, 212 S&P mid-cap and 202 S&P small cap firms.…”
Section: Sample Descriptive Data and Correlationsmentioning
confidence: 55%
“…Chambers et al (2007) demonstrate the total OCI is value-relevant in the post-SFAS 130 adoption years. They further observe investors pay greater attention to OCI information reported in the statement of changes in stockholders' equity.…”
Section: The Effect Of Sfas No 158 On Financial Statement Informationmentioning
confidence: 87%
See 3 more Smart Citations